Genealogy and migration of the Va Ka Valoyi people of Limpopo Province, South Africa - Mathebula, Mandla Darnece (My University, 2018)
The purpose of this study was to investigate the genealogy and migration of the va ka Valoyi people of Limpopo Province, South Africa. Qualitative, narrative research was used to study the oral history of the va ka Valoyi to determine the origin, migration routes and the genealogy of the 20 (twenty) communities of the va ka Valoyi in Limpopo. Data collection was done using semi-structured questionnaires. An initial list of 20 (twenty) respondents was drawn and through Snowball Sampling, the list was increased as per referrals made by the 20 (twenty) respondents during their individual interviews. At the end of the research, 67 (sixty-seven) respondents had been interviewed and secondary sources also consulted. The study has reconstructed the history of the va ka Valoyi, which had not been written before and managed to fill some gaps in the history of their associate groups that historians had not been able to fill in the past. The findings revealed that all the 20 (twenty) communities of the va ka Valoyi in Limpopo are related and identified the various relationships among them. It also revealed how the va ka Valoyi are related to ancient dynasties of the Munhumutapa, Changamire and Torwa and how they reached the Limpopo Province. KEY CONCEPTS Genealogy; Migration; va ka Valoyi; Arrival in Limpopo Province; Oral history.
Thesis (Ph.D. (History)) -- University of Limpopo, 2018
Keywords: Genealogy; Migration; Va ka Valoyi; Oral history; Genealogy; Oral history; Emigration and immigration